1990
DOI: 10.1007/bf00114706
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analyses of spring wheat (CIMMYT cv. PCYT-10) somaclones

Abstract: The objectives of this study were to induce callus from single immature wheat embryos, produce multiple seedlings from the induced callus, and analyse the somaclonal regenerants for potential grain production in a space garden. Immature wheat, Triticum aestivum L. (cv. PCYT-10), embryos were excised 10 to 12 days post-anthesis and cultured on modified Murashige & Skoog's inorganic salts. Embryos cultured on medium containing kinetin (6-furfurylaminopurine) at 0.5mgl -~ plus 2 or 3mgl -~ dicamba (1-methoxy-3,6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 31 publications
0
0
1
Order By: Relevance
“…In Solanum, various authors have reported that somaclonal variation affects noteworthy traits such as resistance to tuber soft rot and root-knot nematodes (Taylor et al 1993;Grammatikaki et al 1999), nutrition quality (Langille et al 1998) and agronomic traits (Thieme and Griess 1996). Despite the great plasticity of the potato genome (Hasim et al 1990;Abe et al 1999;Jain 2001), we did not observe shifts in terms of resistance to late blight in any of the regenerated plants tested (data not shown), and all genotypes showed the same high resistance level as their parents, revealing for this trait a ''silent nature'' of the changes observed. However, some gene changes might not have been observed at a morphological or physiological level because the structural differences in the gene product may not have altered its biological activity sufficiently to result in a modified phenotype.…”
Section: Discussioncontrasting
confidence: 68%
“…In Solanum, various authors have reported that somaclonal variation affects noteworthy traits such as resistance to tuber soft rot and root-knot nematodes (Taylor et al 1993;Grammatikaki et al 1999), nutrition quality (Langille et al 1998) and agronomic traits (Thieme and Griess 1996). Despite the great plasticity of the potato genome (Hasim et al 1990;Abe et al 1999;Jain 2001), we did not observe shifts in terms of resistance to late blight in any of the regenerated plants tested (data not shown), and all genotypes showed the same high resistance level as their parents, revealing for this trait a ''silent nature'' of the changes observed. However, some gene changes might not have been observed at a morphological or physiological level because the structural differences in the gene product may not have altered its biological activity sufficiently to result in a modified phenotype.…”
Section: Discussioncontrasting
confidence: 68%